(3ZfjI GdfRhY Edi Ydej GdCUhd hGdaQhYs - (3GdMdHj, GdMSjfj, CHh GdecGQe, YR GdOjf, MeRI Hf Ydj Hf RgQI, J (B585(3g`s ((3QeVGf Ydj Hf eMeO HGbQs)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje cJGH GdWgGQI GdcdGe aj GdJcdja GdSeYj GYde Cf GdCQcGf ef YHGOGJ GdTQY NeSI(B: (3GdUdGI hGdRcGI hGdUhe hGdML hGdLgGO(B. (3GdUdGI GdTQYjI jMJGL ajgG Edi GdYde HNeSI CTjGA(B...s
(3BNQgG (B:s
... (3hEf Mda GSJMb eG GOYGg hGdCcKQ ef gPG GdNdGa ajg heG ajg efg NdGa bOefG GdOdGdI Ydjg aGYQa Pdc Ef TGA Gddg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\279s
(3GdPQjYI (B16 - 50 ( 346)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis